Headgroup mediated water insertion into the DPPC billayer: a molecular dynamics study - Pandey, Prithvi Raj; Roy, Sudip (Journal of Physical Chemistry B, 2011)
Molecular dynamics simulation was performed on the 1,2-dipalmitoyl-sn-phosphocholine (DPPC) bilayer-water system using the GROMOS96 53a6 united atom force field. The transferability of force field was tested by reproducing the area per lipid within 3% accuracy from the experimental value. The simulation shows that water can penetrate much deeper inside the bilayer almost up to the starting point of the aliphatic chain. There is significant evidence from experiments that water goes deep in the DPPC bilayer, but it has not been reported from theoretical work. The mechanism of insertion of water deep inside the lipid bilayer is still not clear. In this report, for the first time the mechanism of water insertion deep into the bilayer has been proposed. Water transport occurs by the headgroup and its first solvation shell. The trimethyl ammonium (NMe3) group (headgroup of DPPC) has two stable conformations at the bilayer-water interface, one outside the bilayer and another inside it. The NMe3 group has a large clustering of water around it and takes the water molecules inside the bilayer with it during its entry into the bilayer. The water molecules penetrate into the bilayer with the help of the NMe3 group present at the headgroup of DPPC and eventually form hydrogen bonds with carbonyl oxygen present deep inside the bilayer. Structural characteristics at the bilayer-water interface region are also reported.